2016
DOI: 10.5114/wiitm.2016.61429
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of deep biopsy for subepithelial lesions in the upper gastrointestinal tract.

Abstract: IntroductionAccurate diagnosis of subepithelial lesions (SELs) in the gastrointestinal tract depends on a variety of methods: endoscopy, endoscopic ultrasound and different types of biopsy. Making an error-free diagnosis is vital for the subsequent application of an appropriate treatment.AimTo evaluate the efficacy of deep biopsy via the endoscopic submucosal dissection (ESD) technique for SELs in the upper gastrointestinal tract.Material and methodsIt was a case series study. Deep biopsy via the ESD technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 21 publications
(9 reference statements)
0
12
0
Order By: Relevance
“…We performed a systematic review of studies that examined DB via ESD in the diagnosis of GI SETs and found that they demonstrated a high overall diagnostic yield. A subset analysis Current guidelines dictate that GI SETs 20mm require resection, in view of their high probability of malignancy, while GI SETs <20mm are considered benign and EUS surveillance or resection is recommended [5,7,13,15,19]. Factors with high malignancy potential are GI SETs located in the upper or middle portions of the stomach, or when they originate from the muscularis propria level [13,15].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We performed a systematic review of studies that examined DB via ESD in the diagnosis of GI SETs and found that they demonstrated a high overall diagnostic yield. A subset analysis Current guidelines dictate that GI SETs 20mm require resection, in view of their high probability of malignancy, while GI SETs <20mm are considered benign and EUS surveillance or resection is recommended [5,7,13,15,19]. Factors with high malignancy potential are GI SETs located in the upper or middle portions of the stomach, or when they originate from the muscularis propria level [13,15].…”
Section: Discussionmentioning
confidence: 99%
“…In our study population, the overall pooled diagnostic yield of DB via ESD for upper GI SETs was 95% (95%CI 4, I 2 =97%). A majority of the upper GI SETs were located in the stomach (96%, 95%CI 83.77-100, I 2 = 84.6%), followed by the esophagus (2.18%, 95%CI 0.00-10.20, I 2 =77.34%) and Jung et al [16] Vaicekauskas et al [5] Kobara et al [18] Kataoka et al [15] Tae et al [7] Lee et al [17] Overall (I^2 = 78.20%, P = 0.00) Figure 2 Forest plot depicting overall diagnostic yield of deep biopsy via endoscopic submucosal dissection duodenum (1.09%, 95%CI 0.00-4.67, I 2 =36.02%), while none were detected by the gastroesophageal junction within our population (n=209).…”
Section: Overall Diagnostic Yieldmentioning
confidence: 98%
See 3 more Smart Citations